Noninvasive respiratory support following extubation in critically ill adults with obesity: a systematic review and network meta-analysisResearch in context - Joris Pensier; Arthur Naudet-Lasserre; Clément Monet; Mathieu Capdevila; Yassir Aarab; Inès Lakbar; Gérald Chanques; Nicolas Molinari; Audrey De Jong; Samir Jaber (EClinicalMedicine)
Summary: Background: Patients with obesity are at high-risk of extubation failure. Discrepancies were found in the results of recent randomized controlled trials (RCTs) regarding the roles of noninvasive ventilation (NIV), high flow nasal cannula (HFNC) and conventional oxygen therapy (COT) to prevent extubation failure in critically ill patients with obesity. Methods: In this systematic review and network meta-analysis, we searched MEDLINE, Cochrane Center Register of Controlled Trials and Web of Science from 1 January 1998 to 1 July 2024 for RCTs evaluating noninvasive respiratory support therapies (NIV, HFNC, COT, NIV + HFNC) after extubation in critically ill adults with obesity. Primary outcome was reintubation at day 7. Secondary outcome was 28-day mortality. We generated pooled risk ratios (RR) and numbers needed to treat (NNT). We rated risk of bias using the Cochrane risk-of-bias 2.0 tool. The study was registered with PROSPERO (CRD 42022308995). Findings: In seven RCTs including 1933 patients, NIV + HFNC (RR 0.36 [95% confidence interval (CI) 0.16–0.82], NNT = 10 [95% CI 7–33]) and NIV (RR 0.45 [95% CI 0.23–0.88], NNT = 11 [95% CI 8–50]) but not HFNC (RR 0.79 [95% CI 0.40–1.59]) reduced reintubation at day 7, compared to COT. Compared to HFNC, NIV + HFNC (RR 0.46 [95% CI 0.23–0.90], NNT = 14 [95% CI 10–77]) but not NIV (RR 0.57 [95% CI 0.32–1.02]) reduced reintubation at day 7. Compared to HFNC, both NIV (RR 0.31 [95% CI 0.13–0.74], NNT = 15 [95% CI 12–40]) and NIV + HFNC (RR 0.30 [95% CI 0.10–0.89], NNT = 15 [95% CI 11–90]) reduced 28-day mortality. Interpretation: The results suggest that compared to COT and HFNC, NIV alone or with HFNC reduces reintubation in critically ill patients with obesity after extubation. Compared to HFNC, NIV alone or with HFNC reduces mortality. The number needed to treat with NIV or NIV + HFNC to avoid one death was 15. These findings support the application of NIV to mitigate extubation failure in critically ill adults with obesity. Funding: None.